Effectiveness of concise malaria educational training on knowledge, attitudes and practices among patented medicine vendors in Yobe, Nigeria - Katagum, Yahaya Mohammed (2018)
Introduction: Over the years, malaria has been a major global public health and developmental challenge, with approximately 40% of the world's population, within the tropical and sub-tropical regions at risk. Worldwide, malaria accounts for an estimated 207 million cases leading to 627,000 deaths (0.03%) yearly. Furthermore, and paradoxically the disease is preventable, treatable and curable, thereby indicating the mortality figures being very alarming. There are no vaccines yet for malaria prevention, as such public health effort are still geared towards effective protection and drug treatment. In Nigeria, malaria is holo-endemic implying an all year round transmission and the Nigerian control strategies facing setbacks of trained manpower shortages. Thus, non-pharmacist drug retailers called Patent Medicine Vendors (PMVs) were incorporated by government to fill gaps based on WHO recommendations. But however, an assessments of PMVs performances consistently reveals lack of necessary knowledge, attitudes and practices (KAP) to effectively implement government strategies on malaria control.This study aims to evaluate the effectiveness of a developed Concise Malaria Educational Training (CONMET) on KAP among PMVs in Yobe-South district, Nigeria. Methodology:A single-blinded and placebo effected randomised controlled trial was conducted among PMVs in the study location. A process of simple randomization was used to select and assign 292 PMV respondents into the intervention and control arms of study respectively. The development of module was based on the Information-motivation-behavioural (IMB) skills model of health behaviours. Validated pretested questionnaires were used to measure knowledge, attitude and practice at baseline, at immediate, at three months and at six months post-intervention. Data were analysed using IBM SPSS version 23. A One way ANOVA, mixed design ANOVA and Bonferroni tests were used to assess effectiveness of the intervention. P-value of less than 0.05 was considered the point of significance and partial eta square was measure of effect size. Results: Results of the study shows a total response rate of 99.6%. Knowledge, attitudes and practices showed statistically significant relationships with educational levels of respondents (P<0.001), while only knowledge showed significant relationship with attendance of training by PMVs (P = 0.042). A statistically significant effect of intervention on knowledge was achieved in the intervention arm with a large effect size (partial eta ἠ2 = 0.562, p <0.001). The intervention also had a significant effect on respondents attitudes with large effect size (ἠ2 = 0.297, p <0.001) in the intervention group. Similarly, a statistically significant effect of intervention was achieved with respect to respondents malaria practices with a large effect size (ἠ2 = 0.529, p <0.001) in the intervention group as compared to the control group. Conclusion: The CONMET intervention was found to be effective in improving knowledge, attitudes, and practices of the selected respondents. The developed module and training approaches can be adopted by government, regulatory agencies and PMV associations to improve their malaria training curriculum.